Selective Dimensions of Memorable Tourism Experience and Their Influence on Revisit Intention - Verinita, Verinita; Suryaningsih, Ika Barokah; Hendrayati, Heny; Suziana, Suziana; Azman, Heru Aulia (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study explores the influence of Memorable Tourism Experience (MTE) dimensions on tourists’ revisit intention in West Sumatra. While MTE is widely acknowledged in tourism literature, limited studies have empirically disentangled which subdimensions—such as hedonism, novelty, local culture, refreshment, meaningfulness, involvement, and knowledge—are truly consequential in the regional tourism context. Employing an explanatory, cross-sectional design with a purposive sample of 143 respondents, data were analyzed using Partial Least Squares (PLS). The results reveal that only hedonism, local culture, and meaningfulness significantly affect revisit intention. Novelty, refreshment, involvement, and knowledge showed no measurable impact. These findings challenge assumptions that all MTE elements equally drive loyalty, highlighting a more selective emotional-cognitive mechanism in tourist behavior. Practically, local tourism authorities should prioritize emotionally resonant and culturally grounded experiences to strengthen destination appeal and policy alignment with national tourism development goals.